2009
DOI: 10.4049/jimmunol.0803364
|View full text |Cite
|
Sign up to set email alerts
|

Novel Subset of CD8α+ Dendritic Cells Localized in the Marginal Zone Is Responsible for Tolerance to Cell-Associated Antigens

Abstract: Apoptotic cell clearance by dendritic cells (DCs) plays a crucial role in the maintenance of self-tolerance. In spleen, CD8␣؉ DCs are thought to be responsible for this phenomenon by phagocytosing circulating apoptotic cells. However, as CD8␣ ؉ DCs are believed to be predominantly localized in the T cell zone, it remains unclear how these DCs phagocytose blood-borne apoptotic cells accumulated in the marginal zone (MZ). In this study, we identified a subpopulation of CD8␣ ؉ DCs responsible for tolerance induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
211
2
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 186 publications
(237 citation statements)
references
References 52 publications
20
211
2
2
Order By: Relevance
“…We have previously shown that injection of cytochrome c selectively kills cross-presenting cells in an Apaf-1 (apoptosome)-dependent way [19], based on the rationale that only cross-presenting cells would translocate cytochrome c from the endosome into the cytosol (where the apoptosome is formed). It has been shown that cytochrome c preferentially kills CD103 hi CD8 1 DCs [7]. We also observed similar findings for CD8 1 DCs from WT and GMtg mice (unpublished data).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…We have previously shown that injection of cytochrome c selectively kills cross-presenting cells in an Apaf-1 (apoptosome)-dependent way [19], based on the rationale that only cross-presenting cells would translocate cytochrome c from the endosome into the cytosol (where the apoptosome is formed). It has been shown that cytochrome c preferentially kills CD103 hi CD8 1 DCs [7]. We also observed similar findings for CD8 1 DCs from WT and GMtg mice (unpublished data).…”
Section: Discussionsupporting
confidence: 88%
“…For example, in one report, all spleen CD8 1 DCs express high levels of CD103 [18]. In another report, about half of the spleen CD8 1 DC express high levels of CD103 [7]. We find that in our colony of B6 mice, only 10-30% of CD8 1 DCs express appreciable levels of CD103.…”
Section: Discussionmentioning
confidence: 42%
See 3 more Smart Citations